HEALTH EDUCATION ABOUT EXCLUSIVE BREASTFEEDING FOR BABIES 0-6 MONTHS IN SIGUMURU VILLAGE - siregar, nurelilasari; Ritonga, Nefonavratilova (Universitas Aufa Royhan Di Kota Padangsidipuan, 2021)
Breastmilk (ASI) is the most perfect food for babies up to 6 months old, because breast milk contains enough of all the nutrients that babies need. The average rate of exclusive breastfeeding in the world is only around 50%. Based on the results of the 2018 Riskesdas, the proportion of breastfeeding patterns for infants aged 0-5 months in Indonesia is 37.3% exclusive breastfeeding, 9.3% partial breastfeeding, and 3.3% predominant breastfeeding. Observations in Indonesia showed that 63% of breastfeeding only in the first month, 45% in the second month, 30% in the third month, 19% in the fourth month, 12% in the fifth month and decreased drastically in the sixth month, which was only 6%, even more than 200,000 babies or 5% of the infant population in Indonesia at that time were not breastfed at all. The purpose of this community service is so that breastfeeding mothers can know and understand the benefits of exclusive breastfeeding. Socialization is carried out using posters and distributing leaflets. The population and sample of this service are all breastfeeding mothers in Sigumuru Village with a total of 38 people. The results of this community service were enthusiastically received by breastfeeding mothers as seen from the many mothers who asked about information about the benefits of breastfeeding. It is recommended that health education activities in an effort to increase public understanding about exclusive breastfeeding can be carried out regularly with a more frequent frequency and the range of information dissemination can also be expanded to families and community leaders.